Analisis Alih Kode dan Campur Kode Pada Novel "Bercinta Dalam Tahajjudku" Karya Anshela - Cyntia Paramita; Ita Kurnia; Donada Cecilia Avondy; Yuny Yuny (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The research article aims to explore the instances of code switching and code mixing found in the novel "Bercinta Dalam Tahajjudku" by Anshela. This novel exhibits the use of multiple languages, influenced by factors involving both speakers and their interlocutors. In this storyline, Jade and Rintis, being of the same age, frequently use informal language. Therefore, the occurrences of code switching and code mixing in "Bercinta Dalam Tahajudku" by Anshela can serve as viable educational resources for high school settings due to their alignment with linguistic, psychological, and socio- cultural aspects. This novel is suitable as supplementary material because the author's language is accessible for readers, especially students. Through instances switching between different languages and blending them, this novel aids in broadening students' perspectives and knowledge, providing insights into linguistic structures and elements. Keywords: , ,